Sustainability Reporting on Financial Performance of Sri Lankan Listed Companies: How Strong is the Impact? - Weerarathna, Ranitha Sachinthana; Lokeshwara, Anuja Akalanka; Sandali, Weerarathna Arachchi Patabendige Limalka; Chandula, Gunathilake Walallawita Kankanamge Nisal; Nirman, Marasinghe Arachchige Chathushka (Indonesian Journal of Sustainability Accounting and Management, 2021)
This study seeks to examine and identify the impact of sustainability reporting (SR) on the financial performance (FP) of listed companies in Sri Lanka. Data were collected from annual reports of listed companies where sustainability is disclosed in line with the Global Reporting Initiative (GRI) framework. A quantitative approach was used to gather relevant data of the entire population of 289 companies listed on the Colombo Stock Exchange, representing 20 different market sectors. Following purposive sampling, 55 listed companies were ultimately considered, based on the report preparation of those companies having been in line with the GRI framework from 2015/16 to 2018/19. SR was gathered through content analysis based on G4 and GRI standards and measured using an SR index. The authors measured FP using return on assets (ROA). After collecting the data, the authors analyzed it with panel data regression. Findings revealed an insignificant negative impact of SR on the FP of the listed companies in Sri Lanka. Further, researchers identified the impact of each disclosure of SR on FP and identified mixed results.